Oral health of chemotherapy patients before and after provision of oral hygiene instructions at a tertiary care hospital: pre-post design - Mashal Amin; Farhan Raza Khan; Asad Allana; Rubina Barolia; Iqbal Azam (BMC, 2024)
Abstract Objective Disturbances in the oral mucosa is a major concern among patients undergoing chemotherapy. One of the most significant barriers in the implementation of oral care is the lack of knowledge. The aim of the study was to assess gingival and periodontal health status of chemotherapy patients before and after the provision of oral hygiene instructions. Methods A single group, pre-post test was conducted to assess oral health status of patients at the daycare chemotherapy, Aga Khan University Hospital, Karachi, Pakistan. Oral hygiene instructions were given with study models and leaflets. Patients were followed for 6-weeks. Oral health was assessed by using Simplified-Oral Hygiene Index (OHI-S) and Community Periodontal Index (CPI). Differences in indices were analyzed in STATA version-15.0 using Generalized Estimating Equation (GEE) and Wilcoxon Signed-rank test. Results Out of 74, 53 (72%) patients completed study follow-up. Improvement in the OHI-S was found in 14 (26%) patients (p-value < 0.001). GEE showed that age [adjusted OR = 1.10; 95% CI: 1.03-1.11], current chemotherapy cycle [adjusted OR = 1.19; 95% CI: 0.98-1.46], highest education level [Adjusted OR = 1.37; 95% CI: 1.08-12.7] and cancer therapy [Adjusted OR = 0.12; 95% CI: 0.24-0.55] were significantly associated with the change in OHI-S. Wilcoxon signed-rank test showed positive changes in the CPI (p-value < 0.001). Conclusions Basic oral hygiene instructional intervention can be effective in improving the oral hygiene of chemotherapy patients. Nurses should also play a key role in providing psychological and nutritional support to patients.